Contrastive foot structure in Franconian tone-accent dialects*. Issue 1 (15th June 2016) - Köhnlein, Björn
Abstract : Franconian has a contrast between two tone accents, commonly referred to as Accent 1 and Accent 2. Traditional autosegmental analyses of the phenomenon suggest that this opposition derives from the presence of lexical tone. In contrast to this 'tonal approach', I argue that the Franconian accent contrast is based on contrastive foot structure – there is no tone in the lexicon. This 'metrical approach' not only accounts for the tonal differences between the accents, but also captures a variety of facts that are hard to incorporate into a synchronic tonal analysis, involving morphological alternations between Accent 1 and Accent 2, as well as the effects of vowel duration, vowel quality and consonant quality on accent-class membership. The metrical analysis of these patterns is in line with similar approaches to tone-accent contrasts in North Germanic and Scottish Gaelic.